(untitled) (Bangladesh Journal of Bioethics, 2017)
Do you remember Harambe, the 17-year-old silverback who was shot dead after a boy fell into the gorilla enclosure at the Cincinnati Zoo, Cecil, the lion who was shot with an arrow by an American dentist in Zimbabwe, and Marius, the giraffe who was killed and fed to other animals at the Copenhagen Zoo? Every once in a while, a news story about the human-caused death of an animal sparks global outrage, briefly lights up the comments sections on the internet, and reminds us of the inconsistency in how think about non-human animals. According to the Food and Agriculture Organization of the United Nations, we kill approximately two thousand animals for food per second, not including fish and other marine animals. All of these animals have rich emotional lives that matter to them, and what we do to them is as bad, and often much worse, than what was done to Harambe, Cecil, and Marius. Most farm animals are raised in filthy and unnatural conditions, and are subject to routine mutilations and other mistreatment. They are transported in ways that are at best unpleasant and at worst horrific, and they die violent deaths. Yet, most of us while expressing our moral indignation about the treatment of Harambe, Cecil, and Marius rarely spare a thought for the animals we eat. Morally speaking, there does not seem to be much of a difference between what happened in Cincinnati, Zimbabwe, and Denmark and what happens in factory farms and slaughterhouses in every part of the world, every day. If anything, there was a better reason to kill Harambe namely, to avert danger from a child than there is to kill animals for food. We do not need to consume animal products to live a healthy and fulfilled life. In fact, careful studies have found that a well-balanced plant-based diet decreases the chances of suffering from diseases such as diabetes, heart disease, stroke, and some cancers, and benefits the environment. The way we think about and treat non-human animals is deeply confused, and scholars are in a unique position to provide some clarity. The Bangladesh Journal of Bioethics hence decided to dedicate two special issues to the relationship between human beings and other animals, and asked me to be the guest editor. This is the second of the two special issues, and contains the following five articles: The number of fish killed annually by the fishing industry, even on the most conservative estimate, is more than ten times larger than the number of terrestrial animals killed annually for food, and yet animal advocates largely focus on the latter in their efforts to reduce animal suffering. Bob Fischer (Wild Fish and Expected Utility) does the math and argues that considerations of expected utility call that focus into question. He concludes that animal advocacy organizations owe an explanation of why they are not directing more of their resources to fish. Akande Michael Aina and Ofuasia Emmanuel (The Chicken Fallacy and the Ethics of Cruelty to Non-Human Animals) challenge the common view that non-human animals are mere resources that we can use as we please, and ask whether Peter Singers ethics of animal liberation is a plausible alternative. They think it is not, in part because it denies moral status to non-sentient life, and take another approach that draws from Charles Darwins theory of evolution. They argue that cruelty to non-human animals, with whom they claim we are on an equal moral footing, betrays our trusting and neighborly relationship with them. Iván Ortega Rodríguez (Animal Citizenship, Phenomenology, and Ontology: Some reflections on Donaldsons & Kymlickas Zoopolis) provides a brief summary of the position Sue Donaldson and Will Kymlicka defend in their ground-breaking book Zoopolis, and argues that they are mistaken in failing to consider an important metaphysical difference between human beings and other animals. While human and non-human animals share a common environment, only human interaction constitutes what he calls a world. That difference, however, does not undermine the case for animal rights but rather strengthens it. Rhyddhi Chakraborty (Animal Ethics and India: Understanding the Connection through the Capabilities Approach) takes a critical look at a wide range of legal provisions in Indian law designed to protect non-human animals. She argues that, despite such provisions, nonhuman animals continue to suffer greatly at the hands of human beings in India, which is partly due to the lack of a comprehensive ethical vision. She suggests that the capabilities approach can provide such a vision, and concludes by making a number of policy recommendations to improve animal welfare in India. Robin Attfield and Rebekah Humphreys (Justice and Non-Human Animals) complete their argument for the claim that our treatment of non-human animals is a matter of justice, the first part of which can be found in the previous issue of this journal. I thank the contributors for choosing this journal to share their exciting ideas, and the reviewers for their insightful comments and suggestions. I am also indebted to Professor Shamima Parvin Lasker and Ms. Tahera Ahmed for their cooperation and trust. If you, dear reader, are new to the academic debate over the moral status of non-human animals, and if the two Bangladesh Journal of Bioethics special issues on animal ethics have made you curious, as I hope they did, I would like to recommend to you two classics of the animal ethics literature: Peter Singer, Animal Liberation: A New Ethics for Our Treatment of Animals (New York: New York Review/Random House, 1975); and Tom Regan, The Case for Animal Rights (Berkeley/Los Angeles: University of California Press, 1983). I hope you will enjoy reading through this issue, and I am sending you my warm regards. Rainer Ebert Guest Editor, Bangladesh Journal of Bioethics Department of Philosophy, University of Johannesburg, South Africa Email: rainerebert@gmail.com Webpage: http://www.rainerebert.com